2011
DOI: 10.1002/glia.22274
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and genetic profiling of subpopulations of olfactory ensheathing cells from the olfactory bulb

Abstract: Olfactory ensheathing cells (OECs) play a crucial role during neurogenesis of primary olfactory neurons. Transplantation of OECs is considered as a promising new therapy for central nervous system repair. Nevertheless, OECs are constituted of distinct subpopulations and their role during neurogenesis is not clearly understood. In particular, OECs from the olfactory bulb (OB) constitute a heterogeneous, but not yet isolated and characterized, population of cells. In our study, flow cytometry analyses of primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…First, deprivation of microenvironment induces a loss of the two distinct subpopulations of OECs present in primary OB cultures, leading to a decrease in the recovery of the treated animals [21]. Secondly the rate of OECs is around 70% in primary OB cultures which might not be a limiting factor for functional and anatomical recovery in our SCI model.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…First, deprivation of microenvironment induces a loss of the two distinct subpopulations of OECs present in primary OB cultures, leading to a decrease in the recovery of the treated animals [21]. Secondly the rate of OECs is around 70% in primary OB cultures which might not be a limiting factor for functional and anatomical recovery in our SCI model.…”
Section: Discussionmentioning
confidence: 94%
“…Following transplantation in lesioned spinal cord, OECs were shown to enhance axonal regrowth, regulate astrocyte reactivity, increase angiogenesis and modulate glial scar leading to functional recovery in various models of SCI in rodents [15][19]. However, OECs are constituted of several subpopulations and the role of each of them following transplantation in injured spinal cord is not well described [20], [21]. Specifically, OECs can be obtained from two different regions: olfactory mucosa (OM) and olfactory bulbs (OB) and it appears that OECs obtained from OM (OM-OECs) and OB (OB-OECs) have not the same properties and effects after transplantation in vivo [22], [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OECs from the OB segregate into distinct phenotypic populations when maintained in vitro (Hayat et al, ). Some are spindle‐shaped and Schwann cell‐like, whereas others maintain a flattened astrocyte‐like morphology, and these cell types display differences in their expression of glial markers (Honore et al, ). OECs within the OB and OM have distinct gene expression profiles (Guerout et al, ), but it is currently unclear whether these genetically and spatially separate populations mediate common physiological mechanisms that ensure normal homeostasis and continual neuronal turnover.…”
Section: Introductionmentioning
confidence: 99%
“…OECs in the ONL o are considered to promote growth of axons of olfactory receptor neurons, while OECs in the ONL i guide axons to their respective glomerulus according to the type of olfactory receptor protein expressed [41]. In a recent differential study on OECs sorted by fluorescence-activated cell sorting, this assumption was supported; P75-positive OECs overexpress genes involved in supporting axon growth, whereas OECs with low P75-immunoreactivity overexpress genes involved in axon guidance [44]. We showed that OECs subpopulations also differ in their Ca 2+ signalling properties.…”
Section: Ca 2+ Signalling In Oec Subpopulationsmentioning
confidence: 99%